(untitled) (International Journal of Food and Nutritional Sciences, 2024)
This study is aimed to determine the effect of aqua cultural sludge (ACS) and cow urine as an organic nutrient solution (ONS) on the growth and yield to evaluate the impact of water usage on the development and nutrient uptake of Brassica pekinensis L.(Chinese cabbage) and Lactuca sativa L. (Lettuce) cultivated in a hydroponic system. The treatment used contains a combination of ACS, nutrient solution (AB mix) and cow urine. The highest plant growth, yield and the highest foliage fresh weight was observed in treatment with cow urine, with values of 1kg (Chinese cabbage), 300 g (lettuce). It was concluded that a mixture of ACS and cow urine has the potential to reduce the inorganic fertilizers use as a nutrient solution in a hydroponic system.